British Economic Development in South East Asia, 1880-1939 - Sunderland, David (London : Routledge, 2016)
This collection focuses on the economic development of the areas of SE Asia with which Britain had a trading relationship. Covering 1880-1939, the economic growth of the region is revealed through a selection of rare primary resources organized thematically with sections dedicated to agriculture, mining, trade, labour, finance and infrastructure.
volume 1. General introduction agriculture -- volume 2. Mining, trade and industry -- volume 3. The building blocks of development : governance, transport and communications, and human and financial capital index.
First published 2014 by Pickering and Chatto (Publishers) Limited.
Includes bibliographical references.
Keywords: Economic development -- Southeast Asia -- History -- 19th century -- Sources; Economic development -- Great Britain -- History -- 19th century; Great Britain -- Commerce -- Southeast Asia -- History -- 19th century -- Sources